Application of an Online Combination Exercise Intervention to Improve Physical and Mental Health in Obese Children: A Single Arm Longitudinal Study - Ding, Meng; Yi, Xiangren; Yan, Peisai; McDonough, Daniel J.; Gao, Zan; Dong, Xiaosheng (Frontiers in Psychology, 2021)
Background: Childhood obesity has become a public health concern globally in the past decade. The purpose of this study was to explore the effectiveness of an online combination exercise intervention in improving physical and mental health in obese children. Methods: This study adopted a one-group pre-test and post-test research design. A total of 28 obese children from 6 elementary schools in Heze City, Shandong Province, China were recruited. All participants received an 8-week online combination exercise intervention and were tested at three-months follow-up. Participants were tested and surveyed on demographic, feasibility, and obesity indicators, and mental health and quality of life questionnaires. The data were statistically analyzed by one-way analysis of variance with repeated measures. Results: 26 obese children (Meanage = 10.15 years) completed the study. The retention rate reached 92.9% during the entire trial (2 obese children withdrew due to inability to exercise) and no adverse events were reported. In addition, all obese children completed 25/32 (78.1%) of the online courses. After 8 weeks of the intervention, the changes of body fat percentage of obese children (mean difference [MD] = -3.126, p < 0.001, Cohen’s d = -1.777), thinking dimension score (MD = 1.654, p < 0.001, Cohen’s d = 0.603), total quality of life score (MD = 6.385, p < 0.05, Cohen’s d =0.610) and the score of the work attitude dimension (MD = 1.346, p < 0.001, Cohen’s d = 0.744) showed significant differences as compared to baseline. Yet, no significant differences were identified between post-intervention and three-month follow-up measurements (p > 0.05) and we assumed that the intervention effect was maintained three months after the intervention. Conclusions: An online combination exercise intervention is safe and feasible for obese children in improving mental health and quality of life and may have long-term health benefits.